Assessing organizations readiness toward business intelligence systems: a proposed hypothesized model - Anjariny, Ahmed H.; Zeki, Akram M.; Hussin, Husnayati (2012)
Nowadays, the concept of Business Intelligence (BI) is being implemented within many organizations around the globe. Organizations invest billions of US dollars aiming to improve their timeliness and quality of the input to the decision process, where BI is the targeted keyword. However, organizations are often faced with many challenges in achieving the expected outcomes of BI systems within their firms. Here, one of the most cumbersome obstacles is the organizations’ readiness toward BI systems. Therefore, it is highly justified to assess organization’s readiness toward BI systems to avoid any loss and to enhance the overall revenue. This paper presents a brief history on BI systems and the challenges of their implementation within organizations. A review and analysis of models for assessing organizations’ readiness toward BI systems is established to understand their weakness and strength points. Finally, this paper proposes a hypothesized framework for solving readiness assessment issues within organizations which will be evaluated in the coming studies.